Citizen sector transformed : what it means for you - Drayton, Bill.; Global academy for Entrepreneurship; Rooy Media; SKOLL Foundation (ASHOKA Innovators for the Public.)
Bill in this video discusses the sector's rapid rise and its profound implications for business,government leaders, citizen groups, and educators.
DVD.
Keywords: Social change; Social entrepreneurship